Forensic Evidence and the Police, 1976-1980 - Peterson, Joseph L. ([Verlag nicht ermittelbar], 1985)
This data collection focuses on adult cases of serious crime such as homicide (and related death investigations), rape, robbery, aggravated assault/battery, burglary, and arson. Data are included for Peoria, Illinois, Chicago, Illinois, Kansas City, Missouri, and Oakland, California. The data consist of police, court, and laboratory records from reports submitted by police personnel during investigations of suspected criminal offenses. The primary source of information was police case files. Prosecutor and court files were reviewed for information regarding the disposition of suspects who were arrested and formally charged. Crime laboratory reports include information concerning the evidence submitted and the examiner's worksheets, notes, and final results. There are eight files in this dataset. Each of the four cities has one file for cases with physical evidence and one file for cases in which physical evidence was not collected or examined.